Adventures in Criminal Justice Research : Data Analysis Using SPSS 15.0 and 16.0 for Windows. - Logio, Kim A. A. (Online access: SAGE SAGE Research Methods Core., 2008)
The only book of its kind, this text guides students through the process of conducting criminological data analysis. Used primarily in lab settings, the Fourth Edition of Adventures in Criminal Justice Research, derived from the popular Adventures in Social Research (Babbie et al, Pine Forge Press/SAGE), systematically takes students through a series of investigative adventures. More than 150 screenshots in the text offer clear visual step-by-step instructions to solidify student understanding. New to This EditionIncorporates even more criminal justice exercises, pol.